Chronic energy deficiency prevention model for adolescent girls - Khusnul Rohmah Budiarti; Reni Zuraida; Wuryaningsih Dwi Sayekti (Nursing and Health Sciences Journal (NHSJ), 2025)
Adolescence is a critical developmental phase marked by rapid physical growth, requiring adequate nutrition to support reproductive health. However, many adolescents fail to meet their nutritional needs, contributing to a high prevalence of Chronic Energy Deficiency (CED), particularly in developing countries like Indonesia. In Lampung, the prevalence of CED among women of reproductive age is 11.28%, with Islamic boarding schools (pesantren) reporting even higher rates, reaching 30%. This study examines the prevalence of CED at Darul 'Ulum Islamic Boarding School, Central Lampung, identifies contributing factors, and develops a prevention model. A total of 87 randomly selected female students across education levels participated. Data collection involved questionnaires assessing knowledge, attitudes, peer support, fasting habits, length of stay, food recall forms, and mid-upper arm circumference (MUAC) measurements. The findings indicate a 52% prevalence of CED, with significant correlations between CED and knowledge, attitudes, nutritional intake, education, physical activity, fasting habits, and peer support. Multivariate analysis highlights attitudes, fat intake, and length of stay as key factors. The study proposes a prevention model emphasizing behavior change, improved nutrition, and enhanced environmental management to reduce CED prevalence in Islamic boarding schools.